AJARAN ETIKA ISLAM DALAM PEMASARAN PRODUK MURABAHAH (Studi pada Bank Muamalat Indonesia Cabang Malang) - Asnawi, Nur (Fakultas Ekonomi, UIN Maliki Malang, 2009)
A lot of people on business community want to get maximal profit but in practice they ignore normative and ethic values. This condition becomes a life style in public and has grown as Al-Khub al-dunya, Al-takatsur, consumerism, and hedonism. The purpose of this research is to describe ethic comprehension of BMI community and its implication to murabahah product marketing. This research uses field research with qualitative approach. The result shows that BMI Malang branch understand to the importance of ethic application on business activity because it can support sustainable and establishment of the business. The implication of ethic comprehension is reflected in service to customer particularly on murabahah transaction. These service are friendly, honest without differentiate customer who comes to BMI Malang.